Cortical Auditory Evoked Potentials - Vanaja CS (Journal of All India Institute of Speech and Hearing, 1970)
Electrophysiological measures are used during clinical evaluation to supplement and/or compliment the results of behavioural measures. Cortical auditory evoked potentials (CAEPs) have many clinical appli-cations but are not widely used during clinical evaluation. However, considerable evidence exists in literature recommending the use of CAEPs in clinical practice. This article summarises these evidences highlightingits strengths and limitations. The protocol recommended for recording CAEPs in clinical practice is also brie y discussed.